(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
The aims of this research were (1) to study morphology and usefulness of “Pharangkrang”, (2) to maintain this plant, (3) to transfer this knowledge to Samokae community (SC) by workshop CIPP Model Project and (4) to evaluate this project. It has been studied by observation, by reviewed literature, and compared with manual guide botanical book. It was maintained in laboratory, too. The knowledge was transferred to 34 persons by lecturing and training. The results show, that the local name of this tree is” Pharangkrang” in SC, while the scientific name is Psidium guajava. It is dicotyledon plant, that grows about 2 meters high. The stem is brownish gray, the leave is simple, oval shape without stipule, rough, entire margin and rather dark red. The two pairs of leaves are decussate. The netted vain is red, the pink flower is solitary, perfect, regular and complete flower. The ovary is in inferior receptacle. The fruit is simple, typical beery, round, small, dark red with smell, but the interior is pink. Seeds are strong, small and no food collection. In Thailand it has become a decoration plant because of its beauty. Herbarium and pickled green are used to keep it. 10 branches castration have grown in SC. Overall of this project it is in the high level (X=3.88, S.D=0.62).